Implementasi Prinsip-Prinsip Manajemen Dakwah Pada Komunitas Berani Hijrah Dalam Meningkatkan Kesadaran Remaja Tentang Bahaya Pergaulan Bebas - Pasaribu, Nurhasanah; Samosir, Hasrat Efendi (Universitas Cokroaminoto Yogyakarta, 2025)
Free association among adolescents is a social issue that is increasingly worrying in the midst of modern developments. This study aims to examine the implementation of da'wah management principles in the Tanjung Morawa Dare to Hijrah Community in raising adolescent awareness of the dangers of free association. This descriptive qualitative study used interviews and literature study as data collection techniques. The results show that the Dare to Hijrah Community actively applies the principles of consolidation, coordination, tajdid, and ijtihad in all their da'wah programs. The implementation of these principles is realized through various activities such as halaqah (Islamic gatherings), online studies, social programs, and contemporary approaches to adolescents. The consistent application of da'wah management principles has proven effective in fostering adolescent character, strengthening religious understanding, and guiding them away from free association and returning to Islamic values.